The prevalence of risk for hearing impairment in newborns with congenital syphilis in a newborn hearing screening program (NHS) - Oliveira, Thalita da Silva; Dutra, Monique Ramos Paschoal; Nunes-Araujo, Aryelly Dayane da Silva; Silva, Aline Roberta Xavier da; Oliveira, Gabriel Barros Lins Lelis de; Silva, Gleyson José Pinheiro Caldeira; Valentim, Ricardo Alexsander de Medeiros; Balen, Sheila Andreoli (Frontiers in Public Health, 2023)
Objective To study the prevalence of risk for hearing impairment in neonates with congenital syphilis in a newborn hearing screening program. Study design The study design is retrospective, documentary, and is cross-sectional. The sample consisted of newborns who were born between January 2019 and December 2021 and who underwent neonatal hearing screening in a public maternity hospital. Demographic data and the presence and specification of risk indicators for hearing impairment (RIHL) were collected. In retest cases, the results and the final score were also collected. For data analysis, the Kruskal–Wallis and Conover-Iman post-hoc tests were used, comparing the groups that passed and failed the hearing screening that had RIHL, using a significance level of p of <0.5. Results Among the RIHL observed in the sample, prematurity was more frequent in newborns who passed the screening (55.26%) than in those who failed the test (45.67%). Congenital syphilis was the ninth most frequent RIHL (8.04%) among the newborns who passed the test and the 15th factor (3.03%), with the highest occurrence in those who failed the hearing screening. When comparing the two groups (pass and fail), we found significant differences (p < 0.05) between them. Conclusion Congenital syphilis was the ninth risk indicator for the most common hearing impairment and, in isolation, did not present a risk for failure in neonatal hearing screening. Notably, congenital syphilis can cause late hearing loss during child development. Thus, there is an indication of audiological monitoring of these neonates.